CRISPR/Cas therapeutic strategies for autosomal dominant disorders - Caruso, Salvatore Marco; Quinn, Peter M.J.; da Costa, Bruna Lopes; Tsang, Stephen H. (The Journal of clinical investigation, 2022)
Autosomal dominant disorders present unique challenges, as therapeutics must often distinguish between healthy and diseased alleles while maintaining high efficiency, specificity, and safety. For this task, CRISPR/Cas remains particularly promising. Various CRISPR/Cas systems, like homology-directed repair, base editors, and prime editors, have been demonstrated to selectively edit mutant alleles either by incorporating these mutations into sgRNA sequences (near the protospacer-adjacent motif ["near the PAM"]) or by targeting a novel PAM generated by the mutation ("in the PAM"). However, these probability-based designs are not always assured, necessitating generalized, mutation-agnostic strategies like ablate-and-replace and single-nucleotide polymorphism editing. Here, we detail recent advancements in CRISPR therapeutics to treat a wide range of autosomal dominant disorders and discuss how they are altering the landscape for future therapies.